Psychometric properties and invariance of the self-efficacy for writing scale in Peruvian high school students - León-Gutiérrez, Matilde; Morales-García, Wilter C.; Morales-García, Mardel; Jaimes-Soncco, Jania; Saintila, Jacksaint; Mamani, Percy G. Ruiz (Frontiers in Education, 2023)
Introduction Being able to write is a key competency in educational models; therefore, it is important to have a scale to assess writing self-efficacy. Objective The study evaluated the internal structure, providing evidence of reliability, validity, and factorial invariance of the self-efficacy for writing scale (SEWS) across sex and age in Peruvian schoolchildren. Methods An instrumental study was carried out on 1,107 Peruvian adolescents (early, middle, and late) of school age. A confirmatory factor analysis was carried out and the factorial invariance for sex and age was evaluated. Results A good fit was obtained for the total sample (χ2 = 1229.08, df = 101, CFI = 0.997, TLI = 0.997, RMSEA = 0.057 [90% CI: 0.0540.059], and SRMR = 0.029) and presented good α, ω, and H reliability (>0.89). Correlations between another measure of writing self-efficacy (p = 0.76; p < .01), study satisfaction (p = 0.31; p < .01), and burnout (p = −0.12; p < .01) scales supported convergent and concurrent validity. Multigroup factor analysis supported strict invariance for sex and age, for which the SEWS provides evidence of validity and reliability. Discussion This adaptation of the SEWS is a valid, reliable, and invariant measure that can be considered for assessing self-efficacy for writing in Peruvian high school students.